Crafting an Indigenous nation : Kiowa expressive culture in the progressive era - Tone-Pah-Hote, Jenny (The University of North Carolina Press, 2019)
"In this in-depth interdisciplinary study, Jenny Tone-Pah-Hote reveals how Kiowa people drew on the tribe's rich history of expressive culture to assert its identity at a time of profound challenge. Examining traditional forms such as beadwork, metalwork, painting, and dance, Tone-Pah-Hote argues that their creation and exchange were as significant to the expression of Indigenous identity and sovereignty as formal political engagement and policymaking. These cultural forms, she argues, were sites of contestation as well as affirmation, as Kiowa people used them to confront external pressures, express national identity, and wrestle with changing gender roles and representations"--